Evaluation of maxillary sinus septal type and height in partially edentulous maxilla using spiral computed tomography - Hadi, Farah A; Najm, Areej A; Kadhum, Mohammed A (Journal of Baghdad College of Dentistry, 2014)
Background: The presence of anatomic variations within the maxillary sinus such as septa has been reported to increase the risk of sinus membrane perforation during sinus elevation procedure for implant placement. This study aimed to measure the septal heights and correlate it with different types of septa. Material and methods: Thirty patients (15 males and 15 females) with partially edentulous maxillae and mean age (35) years were enrolled in this study. Sixty sinuses scanned with Spiral multislice Computed Tompgraphy, septal height measured after evaluation of septal type whether it was primary or secondary. Results: The results showed that 72.5 % of the septa detected were primary and this is statistically significant when compared with the percentage of secondary type (27.5%). There was a statistically significant difference in the height of septa between the two types, and the primary septa were higher. There was no significant difference between septal type and sex. Conclusions: A sound knowledge of maxillary sinus anatomy and anatomic variations such as septa is essential to prevent complication during surgical interventions involving this region.